Explaining Skills of Islamic Religious Education (PAI) and Character Education Teachers for Grade XI at SMA Negeri 1 Lembah Gumanti - Ayunda Azizah Putri; M Isnando Tamrin; Siska Yulia Rahmi; Yulia Rahman (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Islamic Religious Education teachers are more dominant in using explanation skills in delivering material and more teachers play a role in explaining the material compared to students who search independently. This study aims to determine the implementation of explaining skills (Explaining Skills) of Islamic Religious Education teachers and Budi Pekerti and the obstacles faced by Islamic Religious Education teachers in explaining the material and the efforts made to overcome these obstacles in class XI of SMA Negeri 1 Lembah Gumanti. This type of research is descriptive qualitative research that describes the explanation skills of Islamic Religious Education teachers and Character. The results of the study in explaining the material, teachers have been able to implement indicators in explanation skills so that children understand the delivery of material by Islamic Religious Education teachers. The obstacles faced by Islamic Religious Education teachers are students' lack of focus, misusing the rules for bringing cellphones to school, students who find excuses to leave the classroom and female students are more active in participating in learning compared to male students. Islamic Religious Education teachers use learning methods that are not monotonous, Islamic Religious Education teachers use interesting media and minimize the use of cellphones or Android.